Musculoskeletal disorders and quality of life for Chilean teachers during the COVID-19 pandemic at the academic year-end - Vega-Fernández, Gustavo; Gonzalez-Torres, Carlos; Solis-Soto, María; Lizana, Pablo A. (Frontiers in Public Health, 2024)
Schoolteachers have reported multiple demands contributing to poor perceptions regarding their quality of life and high rates of musculoskeletal disorders. However, there are few studies about the association between musculoskeletal disorders and quality of life from the end of the academic period during the COVID-19 pandemic.Objective: Evaluate musculoskeletal disorders rates and their association with quality of life perceptions among teachers from the last academic period during the COVID-19 pandemic.A total sample of 161 Chilean schoolteachers was included in a crosssectional study musculoskeletal disorders prevalence was evaluated using the Standardized Nordic Questionnaire, and quality of life was evaluated through the Short-Form 12 Health Survey Instrument. A logistic regression was applied to evaluate the association between musculoskeletal disorders and quality of life perceptions adjusted by gender, age, and contract type.Results: 98% of teachers have suffered from some type of musculoskeletal disorders during the last 12 months, and 64% have had six or more painful regions. Women showed a higher musculoskeletal disorders rate than men. The group of teachers with the most musculoskeletal disorders (≥p50) saw significantly greater risk of low scores on the physical (OR: 2.16; p < 0.05) and mental components (OR: 4.86; p < 0.01) of quality of life, regardless of gender, age, and contract type.Conclusions: High musculoskeletal disorders rates suggest that preventive and informative actions must be taken regarding these disorders in order to protect teachers' mental and physical health, considering the effects of the school year and the COVID-19 health crisis.